Pigment epithelium-derived factor downregulation in oestrogen receptor positive breast cancer bone metastases is associated with menopause. (1st January 2023) - Brook, Naomi; Gill, Jespal; Chih, HuiJun; Francis, Kate; Dharmarajan, Arun; Chan, Arlene; Dass, Crispin R.
Abstract: Pigment epithelium-derived factor (PEDF) has a critical role in bone development and anti-tumour function in breast cancer (BC). As the expression and role of PEDF in BC bone metastases is unknown, we aimed to characterise PEDF in primary and metastatic BC. Subcellular PEDF localisation was semi-quantitatively analysed via immunohistochemistry in patient-matched, archived formalin-fixed paraffin-embedded primary BC and liver, lung, and decalcified bone metastases specimens. PEDF localisation was evaluated in 23 metastatic BC patients diagnosed with ER+, human epidermal growth factor receptor-2 (HER2) negative BC or TNBC. Cytoplasmic ( p = 0.019 ) and membrane ( p = 0.048 ) PEDF was lower in bone metastases compared to primary ER+/HER2- BC. In contrast, nuclear PEDF scores were higher in metastases compared to primary TNBC ( p = 0.027 ), and increased membrane PEDF in metastatic tissue had improved disease-free interval ( p = 0.016 ). Nuclear PEDF was decreased in bone metastases compared to primary ER+//HER2- BC in post-menopausal patients ( p = 0.029 ). These novel findings indicate PEDF plays a role in clinical BC metastasis. Significantly lower PEDF levels in the post-menopausal compared to pre-menopausal setting suggests future PEDF research may have greater clinical importance in the post-menopausal ER+/HER2- BC population. Graphical abstract: Image 1 Highlights: Lower PEDF protein in bone metastases compared to primary ER+/HER2-breast cancer. Nuclear PEDF is reduced in post-menopausal ER+/HER2-breast cancer bone metastases. Increased PEDF expression in TNBC metastases associated with improved DFI.